What is Scirrhia? - P.W. Crous; A.W. Minnis; O.L. Pereira; A.C. Alfenas; R.F. Alfenas; A.Y. Rossman; J.Z. Groenewald (IMA Fungus)
The ascomycetous genus Scirrhia is presently treated as a member of Dothideomycetidae, though uncertainty remains as to which family it belongs in Capnodiales, Ascomycota. Recent collections on stems of a fern, Pteridium aquilinum (Dennstaedtiaceae) in Brazil, led to the discovery of a new species of Scirrhia, described here as S. brasiliensis. Based on DNA sequence data of the nuclear ribosomal DNA (LSU), Scirrhia is revealed to represent a member of Dothideomycetes, Capnodiales, Mycosphaerellaceae. Scirrhia is the first confirmed genus in Mycosphaerellaceae to have well developed pseudoparaphyses and a prominent hypostroma in which ascomata are arranged in parallel rows. Given the extremely slow growth rate and difficulty in obtaining cultures of S. brasiliensis on various growth media, it appears that Scirrhia represents a genus of potentially obligate plant pathogens within Mycosphaerellaceae.